PRODUKSI ELISITOR UNTUK MENSTIMULASI METABOLIT SEKUNDER PADA KULTUR JARINGAN TUMBUHAN - Junairiah, Junairiah; Nimatuzahroh, Nimatuzahroh; Suwito, Hery (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
One method in improving secondary metabolites in plant tissue culture is through elicitation, by adding elicitor to plant cells which is intended to induce and enhance secondary metabolites production. In this research, Trichoderma sp and Penicillium sp grown on amylum and Carboxy Methyl Cellulose (CMC) medium were used as elicitor. The results of this research showed that the best growth of the two fungi was produced on amylum medium, with incubation time six days and one day, wet weight 105,8 g/L and 87,4 g/L respectively.Â Keywords: elicitor, secondary metabolites